Super simultaneous equations #2 Reupload

Algebra Level 2

{ 2 x y = 64 ( 6 x ) 2 + 6 y 4 = 8 y 6 + x y 6 \large \begin{cases} 2^{xy}=64 \\ \left(\dfrac{6}{x}\right)^2+6y-4=8y-6+\dfrac{xy}{6} \end{cases}

Find x + y x y \cfrac{x+y}{x-y}


The answer is 1.4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

From 2 x y = 64 = 2 6 x y = 6 2^{xy} = 64 = 2^6 \implies xy = 6 . Then:

( 6 x ) 2 + 6 y 4 = 8 y 6 + x y 6 Note that x y = 6 ( x y x ) 2 + 6 y 4 = 8 y 6 + 6 6 y 2 + 6 y 4 = 8 y 5 y 2 2 y + 1 = 0 ( y 1 ) 2 = 0 y = 1 \begin{aligned} \left(\frac \blue 6x \right)^2 + 6y - 4 & = 8y - 6 + \frac \blue{xy}6 & \small \blue{\text{Note that }xy=6} \\ \left(\frac \blue{xy}x \right)^2 + 6y - 4 & = 8y - 6 + \frac \blue 66 \\ y^2 + 6y - 4 & = 8y - 5 \\ y^2 - 2y + 1 & = 0 \\ (y-1)^2 & = 0 \\ \implies y & = 1 \end{aligned}

Therefore x + y x y = x y + y 2 x y y 2 = 6 + 1 2 6 1 2 = 7 5 = 1.4 \dfrac {x+y}{x-y} = \dfrac {xy+y^2}{xy-y^2} = \dfrac {6+1^2}{6-1^2} = \dfrac 75 = \boxed{1.4} .

2 x y = 64 = 2 6 x y = 6 y = 6 x 2^{xy}=64=2^6\implies xy=6\implies y=\dfrac 6x

So, ( 6 x ) 2 + 6 y 4 = 8 y 6 + x y 6 (\frac 6x)^2+6y-4=8y-6+\frac{xy}{6}

y 2 2 y + 1 = 0 y = 1 x = 6 \implies y^2-2y+1=0\implies y=1\implies x=6

Hence x + y x y = 6 + 1 6 1 = 1.4 \dfrac {x+y}{x-y}=\dfrac {6+1}{6-1}=\boxed {1.4} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...